artikel ANALISIS FILOLOGIS MANUSKRIP AL-QUR'AN BANGKALAN ABAD KE-19: Studi Komparatif antara Rasm Uthmāni dan Imlā’i - Vika Madinatul Ilmi; Siti Fahimah (STAI AL-ANWAR SARANG, 2025)
This study highlights the differences in the Qur’anic rasm writing system between a manuscript from Bangkalan and the Indonesian Standard Mushaf (MSI). This topic is significant because the manuscript tradition in the Indonesian archipelago does not fully adhere to the rules of rasm ʿUthmānī as formulated by Abu Amr al-Dānī, but instead displays variations that reflect local identity. The main objective of this research is to identify the forms of variation, evaluate the consistency of rasm application in the Bangkalan manuscript, and situate it within the broader framework of Qur’anic transmission in Indonesia. The study employs a qualitative method with a library research approach, using descriptive-comparative analysis of Sūrat al-Baqarah as the sample text. The findings reveal notable differences between the Bangkalan manuscript and MSI, particularly in the use of alif in specific words and the application of the ḥadẓf rule, which do not fully conform to the established standard. These variations indicate that Nusantara manuscripts function not only as vessels for transmitting the sacred text but also as cultural artifacts that embody the dynamics of codicology, philology, and the local history of Qur’anic copying. The study underscores the importance of preserving and examining Nusantara Qur’anic manuscripts, both as valuable academic resources and as an Islamic intellectual heritage that contributes to understanding the diversity of rasm traditions beyond the ʿUthmānī standard.